Relationship between gastritis severity, Helicobacter pylori intensity and mast cell density in the antrum and corpus - Fazilet KAYASELÇUK; Ender SERİN; Yüksel GÜMÜRDÜLÜ; Sema BİRCAN; İlhan TUNCER (Turkish Journal of Gastroenterology, 2019)
-